Synthesis, Characterization of some New 4-Thiazolidinone of Acenaphthoquinone - Muntaha .Y. Hayal; Mahmood Shakir Magtoof (University of Thi-Qar Journal of Science, 2022)
This work summarized with Synthesis  of schiff's bases 1(a-c) from reaction of parent compound acenaphthoquinon with primary amines . Treating of imines compounds with thioglycolic acid was produced  thiazolidinone derivatives 2 (a-c) .The structures of synthesized compounds were confirmed by using some spectroscopic analysis such as FT.IR ,  1H-NMR and 13C-NMR spectral